Neutralize the net-rusher - Human Kinetic (Illnois : Human Kinetic, 2006)
The player who can charge the net and dictate play with crisp volleys is one of the most formidable and intimidating opponents you can face. This video can show you strategic situations used by strong net players, shotmaking and tactics to keep them off balance, and drills and games to reinforce these skills in practice
Title from title screen
Hosted by Paul Annacone
Keywords: Tennis -- Training; Instructional videos